A Novel Ultrasound Thermometry Method Based on Thermal Strain and Short and Constant Acoustic Bursts: Preliminary Study in Phantoms - Omar Gachouch; Bruno Giammarinaro; Teymour Kangot; Caterina Monini; Rémi Souchon (Sensors)
In the field of ultrasound therapy, the estimation of temperature to monitor treatments is becoming essential. We hypothesize that it is possible to measure temperature directly using a constant acoustic power burst. Under the assumption that the acoustic attenuation does not change significantly with temperature, the thermal strain induced by such bursts presents a linear relation with temperature. A mathematical demonstration is given in the introduction. Then, simulations of ultrasound waves in a canine liver model were conducted at different temperatures (from 20 °C to 90 °C). Finally, experimental measurements on phantom samples were performed over the same temperature range. The simulation and experimental results both showed a linear relation between thermal strain and temperature. This relation may suggest the foundation of a new ultrasound-based thermometry method. The potential and limitations of the method are discussed.